Flow Redirection Endoluminal Device (FRED) with or without Adjunctive Coiling in Treatment of Very Large and Giant Cerebral Aneurysms - BALTACIOĞLU, FEYYAZ (SPRINGER HEIDELBERG, 2022)
Purpose Flow diverter stents are gaining wider use in the treatment of complex intracranial aneurysms; however, there are limited data on occlusion and complication rates of flow diverters in very large and giant aneurysms. This study assessed the safety and efficacy of flow redirection endoluminal device (FRED) and FRED Jr. stents in aneurysms >= 20 mm. Methods We retrospectively analyzed all aneurysms >= 20 mm treated with FRED/FRED Jr. between January 2010 and June 2020 from three centers. Endpoints for clinical safety were absence of major stroke, aneurysmal rupture, or death and complete or near-complete occlusion for efficacy. Results A total of 45 patients with very large (28 cases) and giant aneurysms (17 cases) were treated with FRED (41 cases), and FRED Jr. (4 cases) stents. The majority of the aneurysms (40/45, 88.9%) were in the anterior circulation. Adjunctive aneurysm coiling was performed in 21 aneurysms (46.7%). Technical complications were encountered in 4 procedures (8.9%). Ischemic and hemorrhagic complication rates were 6.7% and 8.9%, respectively. There was no case with major stroke. The mortality rate was 8.9%, and all cases were due to hemorrhagic complications from aneurysmal rupture. Median angiographic follow-up was 21.5 months (range 3-60 months). Complete occlusion was achieved in 32 aneurysms (71.1%), and near-complete occlusion in 5 cases (11.1%). Conclusion The use of FRED/FRED Jr. for the treatment of aneurysms >= 20 mm achieved a long-term aneurysm occlusion rate and a safety profile comparable to the large series reported with other flow diverter stents.
Keywords: Endovascular; Flow diverter; Complication; Occlusion; Long-term; PIPELINE EMBOLIZATION DEVICE; CAROTID-ARTERY ANEURYSMS; INTRACRANIAL ANEURYSMS; ENDOVASCULAR TREATMENT; MULTICENTER; DIVERSION; DIVERTORS